Psychodynamic Psychotherapy with Severely Disturbed Adolescents: Changes in Reflective Functioning. (3rd July 2019) - Cropp, Carola; Taubner, Svenja; Salzer, Simone; Streeck-Fischer, Annette
ABSTRACT: Over the last few decades Reflective Functioning (RF) has become an important construct for the understanding and treatment of several patient groups. While RF has been well studied in adult samples, few studies have been conducted on RF in adolescence. The present study is the first examining RF in an adolescent sample of 38 inpatients with comorbid disorders of conduct and emotions. Data were collected in a randomized controlled trial. A severe symptomatology and extremely low RF scores at admission ( M = 1.39) characterized the adolescent patient group. RF scores of the clinical sample were significantly lower than those of non-hospitalized adolescent samples. During the inpatient psychodynamic treatment the adolescents' RF capacities improved significantly ( p = .04). The corresponding within-group effect size was medium ( r = −0.33). The reported results must be regarded as preliminary because of some limitations of the study. Further research on RF in clinical adolescent samples is essential.